71. Universal Instructional Design Principles for Mobile Learning - Elias, Tanya (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The report extends a previous analysis of universal instructional design principles in distance education by applying them to the design of mobile learning. Eight principles with particular relevance for distance education are selected, and their recommendations are discussed in relation to the design of educational materials for a range of mobile devices. The problems and opportunities of mobile learning are discussed as is the need for educators to focus on content design issues rather than on searching for the next new technology.